Fatigue failure analysis of steel wire rope sling based on share-splitting slip theory. (November 2019) - Xue, Songling; Shen, Ruili; Shao, Menglong; Chen, Wei; Miao, Rusong
Abstract: At present, Section integrity hypothesis is mostly used to analyze the mechanical properties and identify the damage of the cable. Based on the actual situation and considering the slip effect between the wires of the cable, two simplified calculation models of the cable are proposed based on the theory of share-splitting slip, and the model parameters are obtained through experiments. Finally, on the background of Lijiang Railway Suspension Bridge in Yunnan Province, the fatigue test of the suspension cable is carried out by using the self-developed testing device which can consider both tension and bending fatigue, and the broken steel wire is further analyzed by means of electron microscopy. The results show that two simplified calculation models of wire rope sling are proposed based on the theory of share-splitting slip, which are close to the results of the original model, but greatly improve the calculation efficiency. Comparing the results of three models, it is found that the three models can reflect the development of the slip and fatigue damage of the wire rope sling, but they have some errors with the test. The fracture morphology of the steel wire is shown by electron microscopy photographs. Highlights: The fatigue failure of the steel wire rope sling was analyzed. A simplified model of wire rope sling is given. The validity of the theory is verified by experimental study.